Analysis of the Tendencies and Opportunities of the Lithuanian Small and Medium Business in Integration Processes - Gineitienė, Zina; Girdenis, Juozapas (Ekonomika, 2003)
The small and medium-sized enterprises (SMEs) have the crucial impact to the growth of economy. SMEs arc one of the most important creator of labour places, as well. These enterprises do not need large capital, they fill up new markets or niches and compete with large firms.This analysis shows that Lithuanian exporting SMEs have better trends of output, than non-exporting ones. The indicators of the production (services) realisation and the dynamics, of employment, showed by exporting SMEs, were better, as well.We used the original computer program Ukrit.pas (which computes and evaluates statistical significant differences by the so-called u-criterion) and found very large statistical differences between exporting enterprises, which enlarged output, production or services realisation and employment, and non-exporting ones. These findings’ show the regular advantage of exporting SMEs.SMEs are an important source of innovation. Small innovative firms have the agility required to respond to rapid technological change and customer needs.Statistics Lithuania conducted a survey of enterprises engaged in innovation activities over the period of 1999-2001. 26,9% of the survey participants over this period proposed for the market product innovations and technological process innovations, another part of the survey participants did not carry out innovation activities. The survey results demonstrate that large enterprises with 250 and more employees were more active in innovation activities (63%). Middle enterprises engaged in innovation activities made up 36%, while small enterprises - 21%. In comparison with the survey conducted in EU, innovation activities of the Lithuanian enterprises are less active.